2023
DOI: 10.1177/03635465231168104
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Blood–Derived Mesenchymal Stem Cells Encapsulated in Autologous Platelet-Rich Gel Facilitate Rotator Cuff Healing in a Rabbit Model of Chronic Tears

Abstract: Background: Successful management of chronic rotator cuff (RC) tears remains a challenge owing to its limited intrinsic healing capacity and unsatisfactory failure rate. Menstrual blood–derived mesenchymal stem cells (MenSCs) have the potential to differentiate into the chondrogenic or osteogenic lineage. Autologous platelet-rich gel (APG), a gel material derived from platelet-rich plasma (PRP), can be applied as a carrier system for cell delivery and also as a releasing system for endogenous growth factors. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Uzieliene et al reported that MenSCs can stimulate a chondrogenic response in BMSCs by secreting activin A and TGF-β, potentially exerting protective effects on cartilage tissue by reducing the release of glycosaminoglycan [ 27 ]. Additionally, Song et al suggested that MenSCs encapsulated in autologous platelet-rich gel led to the regeneration of more mature fibrocartilage at the healing site, facilitating rotator cuff healing in a rabbit model of chronic tears [ 26 ]. Notably, this is the first study reporting the application of MenSCs in disc degeneration repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uzieliene et al reported that MenSCs can stimulate a chondrogenic response in BMSCs by secreting activin A and TGF-β, potentially exerting protective effects on cartilage tissue by reducing the release of glycosaminoglycan [ 27 ]. Additionally, Song et al suggested that MenSCs encapsulated in autologous platelet-rich gel led to the regeneration of more mature fibrocartilage at the healing site, facilitating rotator cuff healing in a rabbit model of chronic tears [ 26 ]. Notably, this is the first study reporting the application of MenSCs in disc degeneration repair.…”
Section: Discussionmentioning
confidence: 99%
“…The ease of acquisition, regardless of ethical issues, and short doubling time make MenSCs an appealing source for clinical applications. Emerging data support the application of MenSCs for cartilage and rotator cuff regeneration in animal models, demonstrating protective effects on ECM and tissue healing [ 26 , 27 ]. However, the understanding of MenSCs’ capacity for disc repair and the associated mechanisms remains limited.…”
Section: Introductionmentioning
confidence: 99%